Pelaksanaan Kursus Biola Di Yamaha Music School Padang - Tri Utari; Tulus Handra Kadir (SENDRATASIK UNP, 2021)
This study aims to determine the implementation of violin courses at Yamaha Music School Padang. The data were obtained during the learning process. Interviews were conducted to violin instructors at Yamaha Music School Padang. In addition, photos during the violin learning process at Yamaha Music School Padang were documented. Based on the research results, the implementation of music courses at Yamaha Music School Padang, especially the violin course, "seems not guided" by the concepts and principles of the Yamaha method. In fact, the materials contained in the Yamaha Music Examination Syllabus as an evaluation of learning outcomes based on YMES clearly describes the achievement of students’ learning outcomes based on YMES. The materials contained in the Yamaha Music Examination Syllabus also evaluate the “readiness” of students towards creative abilities. Likewise, the principle of Emphasis on creativity is increasingly not being noticed in music courses at Yamaha Music School Padang if it is viewed from the 'minimal' 'activity' carried out by Yamaha Music School Padang.